Establishment of Forest Energy Resource Base in Gujarat - Khanchandani, M. S. (Indian Forester, 1981)
This paper outlines the concepts of energy plantations, advantages of biomass energy over fossil and fissionable fuels alongwith the economics of conventional fuels for power generations in Gujarat State, It is concluded that firewood or biomass appears to be economical source of energy provided it can be produced on large scale required for power generation. It is emphasised that decentralised power generation units should be set up with fuel wood powered plants to cut the loss in transmission and distribution. The annual fuel yield in energy plantatations and choice of species is also critically discussed with certain case studies. Assessment studies carried out indicate that about 350 ha of land would be needed to raise energy plantation for feeding one MW power plant. Mobilization land, thus, is a major constraint. However, ways and means to mobilize land for energy plantations in Gujarat are outlined. It is concluded that energy plantations will have alround beneficial effects in mitigating the energy crisis, soil conservation, climate and industrial pollution.